Inverted V-shape Osteotomy with Central Strip Resection: A Simultaneous Narrowing and Vertical Reduction Genioplasty - Kim, Tae Gyu (Plast Reconstr Surg Glob Open, 2014)
BACKGROUND: In East Asian countries, a prominent, long, and squared contour of the lower third of the face is considered unattractive, strong, and masculine. To change such a facial contour into an ovular contour, correction of the chin area is essential to accomplish the overall curve in the mandibuloplasty, and various methods for the horizontal reduction of the chin area have been suggested. The horizontal osteotomy and central strip resection technique, which is the most widely used method, has comparatively little effect and some restrictions. To improve these points, the authors introduced an effective method for simultaneously reducing the width and height of the chin without additional procedures. METHODS: From March 2010 to May 2013, 432 women and 117 men underwent mandibular contouring surgery. Of these patients, 321 needed correction of the chin shape with simultaneous mandibular contouring surgery. Narrowing and vertical reduction genioplasty was performed for these patients using an inverted V-shaped osteotomy with central bony segment resection. RESULTS: Narrowing and vertical reduction genioplasty was successfully performed in all cases. No severe complications were observed. Transient sensory changes of the skin around the chin were observed in 87 patients, but all recovered within 3 months. All of the patients were satisfied with the results. CONCLUSIONS: The method that we introduce in this article is a simple and more effective method for simultaneous reduction of the width and height of the chin without additional procedures. The square and long face was effectively and easily reshaped into a slender ovular contour, and the shape of the chin was changed from square to slender.